Human papillomavirus and Its Association with Other Sexually Transmitted Coinfection among Sexually Active Women from the Northeast of Brazil - Paula Almeida Cunha, Ana; Kassandra Pereira Belfort, Ilka; Pedro Belfort Mendes, Francisco; Rodrigues Bastos dos Santos, Gerusinete; Henrique de Lima Costa, Lucas; de Matos Monteiro, Pablo; Lemos Gaspar, Renata; Borges Ferreira, Mariele; de Sá Ferreira, Alice; Cristina Moutinho Monteiro, Sally; Castello Branco Vidal, Flávia (Interdisciplinary Perspectives on Infectious Diseases, 2020)
Objective. To verify the association between HPV infection and the presence of coinfections (Chlamydia trachomatis, Trichomonas vaginalis, and Neisseria gonorrhoeae) in women in the state of Maranhão. Methods. HPV-DNA detection was performed by the nested PCR, using the primers PGMY09/11 and GP + 5/GP + 6. For the identification of sexually transmitted agents, conventional PCR was performed using the following primers: KL1/KL2 (Chlamydia trachomatis), TVA5/TVA6 (Trichomonas vaginalis), and HO1/HO3 (Neisseria gonorrhoeae). DNA-HPV positive samples were subjected to automated sequencing for genotyping. Results. Among the 353 women evaluated, 204 (57.8%) had HPV-DNA, of which 140 (68.6%) exhibited HPV/STIs, while 64 (31.4%) had the only HPV. T. vaginalis infection showed a positive association with HPV (p=0.003). Women without cervical lesions were predominant (327/92.6%); however, the largest number of lesions was reported in women who had HPV/coinfections (18/8.8%). Multiple regression analysis showed that both HPV only and the concomitant presence of HPV/STI were able to indicate the occurrence of epithelial lesions (R = 0.164; R2 = 0.027). Conclusion. The findings suggest that the presence of T. vaginalis can contribute to HPV infection, and HPV/IST association may influence the development of cervical intraepithelial lesions that are precursors of cervical cancer.